Performance, Reliability and Security Risks of Glazing Subject to Explosive Blast Loading - Stewart, Mark G; Netherton, Michael D (Australian journal of structural engineering, 2006)
Risk assessment techniques need to be developed to quantify the safety hazards and economic losses posed by explosive blast loading, and the assessment of risk mitigation measures. The paper applies a probabilistic risk assessment to explosive blast damage caused by terrorist attacks to built infrastructure. Window glazing is adopted as a typical load-capacity system for detailed analysis. Fragility and blast reliability curves are developed for annealed and toughened glazing, for various threat scenarios comprising combinations of explosive charge weights and stand-off distances. Knowledge of the relative likelihood of these threat scenarios are then used to calculate probabilities of glass failure for a typical building facade. A life-cycle cost analysis is used to assess the sensitivity of the most cost-effective design solution for glazing to the attack probability.